Facilitators and Barriers to Health Workforce Retention in Rural and Remote Setting of Indonesia: A Literature Review - Wienda Kartika, L (KnE Life Sciences, 2019)
Health workforce is a critical component of the nation’s health system. Every country is expected to establish a health system which addresses health inequalities by ensuring health services are accessible to all people, particularly those who are vulnerable and living in disadvantage. Therefore, health workforce availability and accessibility determine the health service coverage, people’s health outcome, and the nation’s socioeconomic development. Moreover, Indonesia is a country which faces a critical shortage and low retention of the health workforce, particularly in the rural and remote settings. This literature review aimed to examine the facilitators and barriers to health workforce retention and to evaluate the current health workforce policies in Indonesia. Methods: A narrative literature review was conducted to find out the factors which determine the willingness of health workers to stay and work in rural and remote settings. A comprehensive systematic literature search was employed using five electronic databases, namely: CINAHL, Medline Ovid, Scopus, Web of Science and ProQuest. The inclusion criteria were: 1) articles in English language; 2) articles published between 2007 and 2017; 3) addressed the facilitators and barriers to health workforce retention as the main concern of the literature being released; 4) studies conducted in Indonesia and other countries that have similar socio-economic condition with Indonesia; 5) the object of the studies was health workers and 6) the studies used primary data. Also, thematic analysis is used to identify, analyze, and report themes within data of the included studies. Results: About 204 articles initially assessed, and 16 articles met the inclusion criteria. They consisted of the mixture of quantitative, qualitative and mix method studies. Seven major themes emerged within the included studies: incentives, career and professional development, working condition, living condition, personal characteristics, political factors and cultural. Thus, by understanding the underlying factors of health workforce retention, key policy-makers can evaluate the current policies and develop a range of useful and comprehensive strategies which address the roots of its problems. Conclusion: According to the findings, there are six broad recommended strategies which address the facilitating factors and barriers for retaining health workforce in rural and remote areas: 1) provide adequate incentives; 2) provide CPD for rural and remote health workers; 3) recruit students from rural background; 4) improve working condition; 5) improve the living condition; and 6) strengthen the role of local government and intersectoral collaboration. Moreover, the government of Indonesia emphasize the incentives and Continuing Professional Development (CPD) strategies to attract and retain health workers to work in rural and remote areas. The deployment strategies employed by the Indonesian government are mostly temporary solutions. These strategies effective to overcome the urgent shortage, but do not address the underlying causes of low retention of health workers in rural and remote settings. The establishment of better living and working condition are necessary to achieve health workforce sustainability in rural and remote settings. Also, the intersectoral collaboration and the strengthening of local government roles, capacity and commitment will succeed the retention intervention. Keywords: Health workforce retention, health policy, rural and remote settings, Indonesia